Adsorption of Fluoride from Water by Use of Powdered Tilapia Fish Scales - Nasiebanda, R.; Wamalwa, E.; Lusweti, K. (Africa Environmental Review Journal, 2020)
Ingestion of adequate fluoride (F-) necessary for healthy bones and teeth is realized through food, soil and water while its excess leads to dental, skeletal and soft tissue damage. Defluoridation is one of the conventional techniques used to protect against fluorosis. In the present study fluoride adsorption from water was done using fish scales collected from Eldoret. These materials were washed, dried, ground, weighed, treated and tested for fluoride removal in water and characterized by FTIR and SEM methods. The effect of F- concentration, adsorbent dosage, contact time, temperature, and pH and agitation rate were also investigated. The results show that the % adsorption of F- on to the powdered fish scales increased from 95% to 99% with corresponding adsorbent mass of 0.5 g/mL and 3 g/mL and a further increase in mass resulted in a constant % adsorption. Additionally, % removal of F- initially increased from 96.7% and attained the highest % adsoption of 98.4 after 1 hour. Furthermore, % adsorption increased from 94.7 with agitation rate of 35 rpm to an optimum agitation rate of 400 rpm with % adsorption of 96. Moreover, fluoride adsorption increased from 94.1% to 96% with increased solution pH of 1 to 7 and then dropped beyond pH 9. Percentage adsorption increased from 95.5-96.4 between a temperature range of 288-313 K, and decreased there after between temperature of 323-353 K. The F- removal increased from 82.6% to 99% between the initial fluoride concentration of 1-10 mg/L, after which the % adsorption remained constant. However, the F- adsorption data correlated to the Freundlich and Langmuir models and could be classified as C-Type according to Giles classification of isotherms. The pseudo-first and pseudo-second order kinetic models and the Weber and Morris intra particle diffusion model equation were applied onto the adsorbent. The adsorbent could be used as a low-cost adsorbent for adsorption of F- ions from aqueous media.